Effects of exercise on vascular remodelling and fetal growth in uncomplicated and abortion-prone mouse pregnancies - Evangeline A. K. Lovell; Shanna L. Hosking; Holly M. Groome; Lachlan M. Moldenhauer; Sarah A. Robertson; Kathryn L. Gatford; Alison S. Care (Scientific Reports)
Abstract Studies in humans and rodents show exercise in pregnancy can modulate maternal blood pressure, vascular volume, and placental efficiency, but whether exercise affects early uteroplacental vascular adaptations is unknown. To investigate this, CBA/J female mice mated with BALB/c males to generate healthy uncomplicated pregnancies (BALB/c-mated) or mated with DBA/2J males to generate abortion-prone pregnancies (DBA/2J-mated), were subjected to treadmill exercise (5 days/week, 10 m/min, 30 min/day for 6 weeks before and throughout pregnancy), or remained sedentary. In uncomplicated pregnancies, exercise caused symmetric fetal growth restriction in fetuses evidenced by reductions in fetal weight, crown-to-rump length, abdominal girth and biparietal diameter. Placental insufficiency was indicated by reduced fetal: placental weight ratio and increased glycogen cell content in the junctional zone of placentas of exercised BALB/c-mated mice on gestational day (GD)18.5. In abortion-prone pregnancy, exercise increased placental efficiency, but the number of late-pregnancy resorptions were elevated. Effects of paternal genotype independent of exercise were evidenced by a greater number of resorptions, poorer spiral artery remodelling, and larger placentas in the DBA/2J-mated compared to BALB/c-mated mice. Effects of exercise independent of paternal genotype included increased implantation sites at both mid and late pregnancy, accompanied by decreased junctional zone areas of placentas. Our findings show that exercise before and during pregnancy in mice can have different effects on fetal outcomes, depending on the paternal and/or fetal genotype. This suggests that the underlying mechanisms are responsive to fetal cues.